Design of smart human following on rail inspection using human pose estimation marker-less motion capture based on blazepose - Ciptaningrum, Adiratna (Journal Geuthee of Engineering and Energy, 2023)
Advances in artificial intelligence (AI) technology today have a significant impact in various aspects of human life. One example is the evolution of robotics that has achieved the ability to follow human movements. To achieve this, AI technology utilizes image recognition through Computer Vision and the Human Pose Estimation method with the help of the BlazePose library, which is able to recognize 33 keypoints in human body poses. Research in this area aims to develop an automatic control system that can be used on inspection carts, enabling them to follow human body movements while walking. The results showed a detection accuracy rate of 84.82% with an optimal detection distance between 4 to 8 meters from the camera, with an average detection accuracy of 89.862%. On the motor control aspect, the system is set to turn off the motor when the distance between the device and the object is in the range of 1-2 meters, and turn it on at a distance of 3-12 meters. However, it is important to note that the accuracy achieved is greatly affected by the color segmentation capabilities of the software, the lighting conditions in the environment, as well as the resolution of the camera used.